Calculation of Directivity Patterns from Spherical Microphone Array Recordings - Anemüller, Carlotta; Herre, Jürgen (147th Audio Engineering Society International Convention 2019, 2019)
Taking into account the direction-dependent radiation of natural sound sources (such as musical instruments) can help to enhance auralization processing and thus improves the plausibility of simulated acoustical environments, as e.g. found in virtual reality (VR) systems. In order to quantify this direction-dependent behavior, usually so-called directivity patterns are used. This paper investigates two different methods that can be used to calculate directivity patterns from spherical microphone array recordings. A comparison between both calculation methods is performed based on the resulting directivity patterns. Furthermore, the directivity patterns of several musical instruments are analyzed and important measures are extracted. For all calculations, the publicly available anechoic microphone array measurements database recorded at the Technical University Berlin (TU Berlin) was used.
herre_papers_virtual_and_augmented_reality_rendering